The Impact of NAFTA on Prices and Competition: Evidence from Mexican Manufacturing Plants - Ayuma Ken Kikkawa; Yuan Mei; Pablo Robles Santamarina (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper assesses the impact of the North American Free Trade Agreement on Mexican manufacturing plants' prices and markups. We distinguish between Mexican goods that are exported and those sold domestically, and decompose their prices separately into markups and marginal costs. We then analyze how these components were affected by reductions in Mexican output tariffs, intermediate input tariffs, and U.S. tariffs. We find that declines in these tariffs led to significant reductions in the marginal costs of Mexican products. However, prices of exported goods slightly increased as exporters increased their markups in response to declines in U.S. tariffs.
Keywords: 330